Comparisons of Threshold EZW and SPIHT Wavelets Based Image Compression Methods - Xiaofeng Wu; Shigang Hu; Zhiming Li; Zhijun Tang; Jin Li; Jin Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Images require substantial storage and transmission resources, thus image compression is advantageous to reduce these requirements. The objective of this paper is to implement the concept of wavelet based image compression to gray scale images using different wavelet techniques. The techniques involved in the comparison process are threshold method, EZW(embedded zerotree wavelet) and SPIHT(set partitioning in hierarchical trees). These techniques are more efficient and provide a better quality in the image.  Matlab is used to be carried out the simu1ation where different wavelet and different methods for image compression are applied. The techniques are compared by using the performance parameters CR (Compression Ratio), PSNR (Peak Signal to Noise Ratio), MSE (Mean Square Error), and BPP (Bits per Pixel). Images obtained with those techniques yield very good results. The results showed that the compression effect of wavelet threshold compression is not good; wavelet decomposition level and wavelet function impact on the compression effect; Wavelet based image compression based on EZW and SPIHT are more efficient. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4437